Early life stress dampens stress responsiveness in adolescence: Evaluation of neuroendocrine reactivity and coping behavior. (May 2016) - Hsiao, Young-Ming; Tsai, Tsung-Chih; Lin, Yu-Ting; Chen, Chien-Chung; Huang, Chiung-Chun; Hsu, Kuei-Sen
Highlights: ELS promotes the development of stress resistance in adolescence. ELS blunts acute stress-induced alterations of hippocampal synaptic plasticity. ELS-induced change in stress reactivity is related to elevated plasma corticosterone. Abstract: Stressful experiences during early life (ELS) can affect brain development, thereby exerting a profound and long-lasting influence on mental development and psychological health. The stress inoculation hypothesis presupposes that individuals who have early experienced an attenuated form of stressors may gain immunity to its more virulent forms later in life. Increasing evidence demonstrates that ELS may promote the development of subsequent stress resistance, but the mechanisms underlying such adaptive changes are not fully understood. The present study evaluated the impact of fragmented dam-pup interactions by limiting the bedding and nesting material in the cage during postnatal days 2–9, a naturalistic animal model of chronic ELS, on the physiological and behavioral responses to different stressors in adolescent mice and characterized the possible underlying mechanisms. We found that ELS mice showed less social interaction deficits after chronic social defeat stress and acute restraint-tailshock stress-induced impaired long-term potentiation (LTP) and enhanced long-term depression (LTD) in hippocampal CA1 region compared with control mice. The effects of ELS on LTP and LTD were rescued by adrenalectomy. While ELS did not cause alterations in basal emotional behaviors, it significantly enhanced stress coping behaviors in both the tail suspension and the forced swimming tests. ELS mice exhibited a significant decrease in corticosterone response and trafficking of glucocorticoid receptors to the nucleus in response to acute restraint stress. Altogether, our data support the hypothesis that stress inoculation training, via early exposure to manageable stress, may enhance resistance to other unrelated extreme stressors in adolescence.